Design and Development of a Real-Time Monitoring System for Highway Road Surface Anomalies - Alagirisamy, Mukil (Journal of Ubiquitous Computing and Communication Technologies, 2024)
The recent unprecedented increase in highway networks in India has increased the need to maintain safe and smooth roads. The increasing number of road surface anomalies such as cracks, surface irregularities, and anomalies can lead to vehicle damage and accidents. This research work presents the design and development of a real-time monitoring system for detecting anomalies in highway road surfaces. The proposed system utilizes the machine vision model integrated with cameras, sensors, and edge computing to provide timely and accurate alerts for the drivers and also to the road maintenance authorities. The proposed solution is designed specially to work under different environmental conditions and enable large-scale deployment. The output generated from the proposed model is visual feedback of the detected anomalies and its severity analysis, enabling quick road maintenance actions.
Keywords: Image Processing; Crack Detection; Neural Networks; Surface Anomalies; Sensors; Edge Computing.